Predictors of condom use among sexually active persons involved in compulsory national service in Ibadan, Nigeria (2007)
Migration is known to increase the risk of heterosexual transmission of human immunodeficiency virus (HIV) in sub-Saharan Africa, but little attention has been paid to fresh graduates of tertiary institutions who are on migration for compulsory national assignment in Nigeria. In July and August 2004, a survey was conducted on sexually active men (n= 344) and women ( = 373) to investigate determinants of condom use during national service. Sixty-eight percent of men and 41% of women reported condom use at last intercourse before the survey. For both men and women, condom use was common if they had one or more regular sex partners and if they were purchasing condoms. In addition, women’s condom use was predicted by being single and having intention to use condoms in next intercourse. The findings further showed that there was high risk of HIV transmission in the sample population as consistent condom use was 15% for men and 4%for women. Twelve percent of men and 8% of women reported STI diagnoses in the last 12 months before the survey. Four percent of men and 2% of women reported they already had HIV diagnoses. Only 1% of men and 2% of women reported they would receive voluntary HIV test if offered free by the government. The study findings suggest the need to extend the existing condom social marketing services in the country to the youth on national service and promote condom education messages among them prior to commencing national service.